2006
DOI: 10.1002/chem.200501540
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Reactivity of Palladacycles That Contain a Chiral Rhenium Fragment in the Backbone: New Cyclometalation and Catalyst Design Strategies

Abstract: The bromocyclopentadienyl complex [(eta5-C5H4Br)Re(CO)3] is converted to racemic [(eta5-C5H4Br)Re(NO)(PPh3)(CH2PPh2)] (1 b) similarly to a published sequence for cyclopentadienyl analogues. Treatment of enantiopure (S)-[(eta5-C5H5)Re(NO)(PPh3)(CH3)] with nBuLi and I2 gives (S)-[(eta5-C5H4I)Re(NO)(PPh3)(CH3)] ((S)-6 c; 84 %), which is converted (Ph3C+ PF6 -, PPh2H, tBuOK) to (S)-[(eta5-C5H4I)Re(NO)(PPh3)(CH2PPh2)] ((S)-1 c). Reactions of 1 b and (S)-1 c with Pd[P(tBu)3]2 yield [{(eta5-C5H4)Re(NO)(PPh3)(mu-CH2PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 93 publications
(38 reference statements)
2
11
0
Order By: Relevance
“…Other types of carbene have successfully been used in promoting the reaction at catalyst loadings of 10 mol ppm or less. A half‐sandwich rhenium cyclopentadienyl palladacycle, a dimeric C,N‐bidentate complex, a P,C‐bidentate ligand, and a NHC with a remote heteroatom, all reported less than 5 results with at least 80% yield using 10 mol ppm or less. In 2008, Joshaghani et al.…”
Section: Suzuki–miyaura Cross‐couplingmentioning
confidence: 99%
“…Other types of carbene have successfully been used in promoting the reaction at catalyst loadings of 10 mol ppm or less. A half‐sandwich rhenium cyclopentadienyl palladacycle, a dimeric C,N‐bidentate complex, a P,C‐bidentate ligand, and a NHC with a remote heteroatom, all reported less than 5 results with at least 80% yield using 10 mol ppm or less. In 2008, Joshaghani et al.…”
Section: Suzuki–miyaura Cross‐couplingmentioning
confidence: 99%
“…We have been interested in developing new types of “organic” chiral hydrogen bond donors that are templated by transition metals. , This is part of a larger program that employs functionally inert or “spectator” metals as architectural units in catalysts with orthogonal active sites. , Such organometallic or coordination compounds can exhibit very high activities and often enantioselectivities. However, our initial results with hydrogen bond donors were disappointing.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a few cases this reaction gives cyclometalated complexes with an unusual trinuclear structure 15,16 which exhibits interesting catalytic applications. [17][18][19][20] We have found that this is the case with ligand a when the reaction is carried out at room temperature. Thus, ligand a can be metalated at an aliphatic or at a sterically hindered aromatic carbon and, in the latter case, it may give di-or trinuclear species, showing an unprecedented and versatile behavior.…”
Section: Introductionmentioning
confidence: 99%